Engineered and hybrid human megakaryocytic extracellular vesicles for targeted non-viral cargo delivery to hematopoietic (blood) stem and progenitor cells - Das, Samik; Thompson, Will; Papoutsakis, Eleftherios Terry (Frontiers in Bioengineering and Biotechnology, 2024)
Native and engineered extracellular vesicles (EVs) generated from human megakaryocytes (huMkEVs) or from the human megakaryocytic cell line CHRF (CHEVs) interact with tropism delivering their cargo to both human and murine hematopoietic stem and progenitor cells (HSPCs). To develop non-viral delivery vectors to HSPCs based on MkEVs, we first confirmed, using NOD-scid IL2Rγnull (NSG™) mice, the targeting potential of the large EVs, enriched in microparticles (huMkMPs), chosen for their large cargo capacity. 24 hours post intravenous infusion into NSG mice, huMkEVs induced a nearly 50% increase in murine platelet counts. PKH26-labeled huMkEVs or CHEVs localized to the HSPC-rich bone marrow preferentially interacting with murine HSPCs, thus confirming their receptor-mediated tropism for NSG HSPCs, and their potential to treat thromobocytopenias. We explored this tropism to functionally deliver synthetic cargo, notably plasmid DNA coding for a fluorescent reporter, to NSG HSPCs both in vitro and in vivo. We loaded huMkEVs with plasmid DNA either through electroporation or by generating hybrid particles with preloaded liposomes. Both methods facilitated successful functional targeted delivery of pDNA, as tissue weight-normalized fluorescence intensity of the expressed fluorescent reporter was significantly higher in bone marrow than other tissues. Furthermore, the fraction of fluorescent CD117+ HSPCs was nearly 19-fold higher than other cell types within the bone marrow 72-hours following administration of the hybrid particles, further supporting that HSPC tropism is retained when using hybrid particles. These data demonstrate the potential of these EVs as a non-viral, HSPC-specific cargo vehicle for gene therapy applications to treat hematological diseases.